THE SPECIFICITY AND IMPORTANCE OF ETIQUETTE IN UZBEK LINGUISTICS (American Journal of Pedagogical and Educational Research, 2023)
This is the study of the means of speech etiquette in the Uzbek language - affixes, lexical units, stable combinations in the light of modern paradigms of linguistics and the necessary means of forming a culture of communication. determined the pedagogical and psychological criteria.